How to help a hungry werewolf - Stein, Charlotte (St. Martin's Griffin, 2024)
"What We Do in the Shadows with the small town feels of Gilmore Girls in this swoon-worthy romance that will leave readers delightfully cozy and hungry for more. When Cassandra Camberwell returns to her hometown of Hollow Brook to clear out her late grandmother's ramshackle old house, the last thing she expects is Seth Brubaker on her doorstep. Her former best friend was responsible for the worst moment of her high school life, and she can't imagine he wants to do anything but torment her all over again. Until she unearths the real reason this annoyingly gorgeous beast of a man keeps hanging around: he's an actual werewolf, who's certain she's the witch that will ease his suffering. But Cassie just isn't sure if she can trust him again. So Seth offers a pact: he'll teach her all about her undiscovered magic, and she will brew the potions he needs. No feelings, no funny business, just a witch and a werewolf striking a deal. Totally doable. Until they get hit with a do-or-die mating bond. And now the heat is rising, in between fights with formers bullies and encounters with talking raccoons. They just have to not give in. Unless giving in just might be the very thing they never knew they always wanted"--